2020
DOI: 10.1371/journal.ppat.1008366
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-mediated apoptosis pathway during WSSV infection in crustacean mud crab

Abstract: MicroRNAs are regulatory molecules that can be packaged into exosomes to modulate cellular response of recipients. While the role of exosomes during viral infection is beginning to be appreciated, the involvement of exosomal miRNAs in immunoregulation in invertebrates has not been addressed. Here, we observed that exosomes released from WSSV-injected mud crabs could suppress viral replication by inducing apoptosis of hemocytes. Besides, miR-137 and miR-7847 were found to be less packaged in mud crab exosomes d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Previous studies on the immunomodulatory functions of exosomes derived from immune-activated murine macrophage cells [37] and the presence of antigenic viral proteins in porcine serum-derived exosomes [38] suggest the future prospects of using exosomes as carriers of therapeutic molecules for inflammatory pain and as candidates for vaccine delivery, respectively. The involvement of exosomal miRNAs in the antiviral immune response in aquatic invertebrates (crustaceans) and evidence for the antiviral role of exosomes in teleosts have also been reported [10,11,13]. Furthermore, secretion of exosomes from antigen-presenting cells with an abundance of immune molecules such as MHCIIβ upon treatment with chemical stimulants such as CpG and differential protein expression patterns in the EVs of S. salar that are released from the infected cells to promote immune responses upon treatment with biological stimulants, such as P. salmonis, has been reported [6,9].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies on the immunomodulatory functions of exosomes derived from immune-activated murine macrophage cells [37] and the presence of antigenic viral proteins in porcine serum-derived exosomes [38] suggest the future prospects of using exosomes as carriers of therapeutic molecules for inflammatory pain and as candidates for vaccine delivery, respectively. The involvement of exosomal miRNAs in the antiviral immune response in aquatic invertebrates (crustaceans) and evidence for the antiviral role of exosomes in teleosts have also been reported [10,11,13]. Furthermore, secretion of exosomes from antigen-presenting cells with an abundance of immune molecules such as MHCIIβ upon treatment with chemical stimulants such as CpG and differential protein expression patterns in the EVs of S. salar that are released from the infected cells to promote immune responses upon treatment with biological stimulants, such as P. salmonis, has been reported [6,9].…”
Section: Discussionmentioning
confidence: 93%
“…The importance of exosomes in terms of having various beneficial roles in physiological processes, as well as detrimental roles in pathological processes in humans and other mammals has been widely discussed within the field of exosome research [5]. Fish exosome research is at a primitive stage, with few reported studies related to aquatic animals [6][7][8][9][10][11][12]. Analyzing body fluids in teleosts can deepen the understanding of exosomes with regard to their secretion into the extracellular fluids, such as plasma, and their biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Given that miRNAs are the most abundant RNA species in exosomes, it has been reported that the molecular composition of the miRNA cargo carried by exosomes can be affected by external signals such as oxidative stress and pathogens infection, which reflects the physiological or pathological state of donor cells [ 40 ]. Our previous study revealed that miR-137 and miR-7847 were less packaged in mud crab exosomes after White spot syndrome virus challenge, which resulted in the activation of apoptosis induce factor and eventually the induction of apoptosis and suppression of viral infection in recipient mud crab hemocytes [ 41 ]. Besides, miR-145, miR-199a, miR-221 and Let-7f that are assembled in exosomes can directly bind to the genomic RNA of Hepatitis C virus to inhibit viral replication in umbilical cord mesenchymal stem cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…At different time post-infection, hemolymph was collected from three randomly chosen crabs per group for further investigation [ 27 ]. For mud crab mortality assays, 10 crabs/per treatment were used, 200 uL of the indicated exosome solution (1×10 8 vesicles/mL) was injected into the base of the fourth leg of each crab according to our previous study [ 41 ]. The cumulative mortality was examined daily.…”
Section: Methodsmentioning
confidence: 99%
“…The role of exosomes has also been investigated in relation to viral infection in crustaceans in particular in the Asiatic mud crab ( Scally paramamosain ) upon infection with White spot syndrome virus (WSSV), that causes huge economic losses in aquaculture [ 38 ]. MiRNAs from exosomes released from WSSV-injected crabs could suppress viral invasion by inducing apoptosis of haemocytes.…”
Section: Exosomesmentioning
confidence: 99%